Поиск национальной идентичности в современной архитектуре Беларуси - Шамрук, А. (Народна творчість та етнографія, 2008)
The ways of searching of national identity, the methods of interpretation of the problem of regional peculiarities in modern architecture have been analyzed in the article. The modes of artistic reflections of the cultural and historical heritage of the past, the interpretation of the traditional regional architecture archaetypes in modern construction in Belarus have been considered. Traditional concept development prospects against a background of innovational technological and artistic strategies application have been pointed out.